Hack Proofing Your Web Applications: The Only Way to Stop a Hacker is to Think Like One - Russell, Ryan (Syngress Media, 2011)
OPEC, Amazon, Yahoo! and E-bay, if these large, well-established and security-conscious web sites have problems, how can anyone be safe? How can any programmer expect to develop web applications that are secure? "Hack Proofing Your Web Applications" is specifically written for application developers and webmasters who write programs that are used on web sites. It covers Java applications, XML, ColdFusion, and other database applications. This focuses not on catching the hackers once they've entered the site, but aims to show programmers how to design tight code to deter hackers from the word go.